Baseline Neutrophil-to-Lymphocyte Ratio Is Independently Associated With 90-Day Transplant-Free Mortality in Patients With Cirrhosis - Liu, Jing; Li, Hai; Xia, Jie; Wang, Xianbo; Huang, Yan; Li, Beiling; Meng, Zhongji; Gao, Yanhang; Qian, Zhiping; Liu, Feng; Lu, Xiaobo; Liu, Junping; et al. (Frontiers in Medicine, 2021)
Background: Patients with cirrhosis have an increased risk of short-term mortality, however, few studies quantify the association between neutrophil-to-lymphocyte ratio (NLR) and 90-day transplant-free mortality in cirrhotic patients. Methods: We prospectively analyzed 3970 patients with chronic liver diseases from two multicenter cohorts in China (January 2015 to December 2016 and July 2018 to January 2019). Restricted cubic splines (RCS) were used to analyze the relation of NLR and all-causes 90-day transplant-free mortality in cirrhosis. Results: A total of 2583 cirrhotic patients were enrolled in our study. RCS showed that the odds ratio (OR) of all causes 90-day transplant-free mortality started to increase rapidly until around NLR 6.5, and then was relatively flat (p for non-linearity <0.001). The risk of 90-day transplant-free mortality in cirrhotic patients with NLR < 6.5 increased with an increment of 23% for every unit increase in NLR (p<0.001). The patients with NLR < 4.5 had the highest risk (OR:2.34, 95% CI 1.66-3.28). In multivariable-adjusted stratified analyses, the increase in the incidence of 90-day transplant-free mortality with NLR increasing was consistent (OR >1.0) across all major prespecified subgroups, including infection group (OR:1.04, 95% CI 1.00-1.09) and non-infection (OR:1.06, 95% CI 1.02-1.11) group. The trends for NLR and numbers of patients with organ failure varied synchronously and were significantly increased with time from day 7 to day 28. Conclusions: We found a non-linear association between baseline NLR and the adjusted probability of 90-day transplant-free mortality. A certain range of NLR is closely associated with poor short-term prognosis in patients with cirrhosis.